Manifestasi Keluarga dalam Membentuk Kepribadian Anak Usia Dini - Mas'udi, Mas'udi (PIAUD Universitas Islam Negeri Sunan Kudus, 2015)
Education will always take place in his journey through the ages. Thiscontinuity of existence dotted beneath the education that will always lead the studentstoward their maturation itself. Directions increasingly globalized education is oneindicator that the direction and quality of education in the future should competewith the dynamics of globalism itself. Globalization is leaning completely to rapidsystem and information technology will rein in education to go hand in hand withthe dynamic development of the runs. Based on the fact, this globality, educationpolicy directions create the best quality of education undoubtedly questionable.The question is also grounded to the probability of an education that will activelywork together on the development period of increasingly rapid and efforts topreserve the culture social adiluhur to be completed. Therefore, the manifestationof moral values and moral education into the general atmosphere that needs to berealized in order to counterbalance an increasingly global world develops rapidly.Families in growth will play an important role to teach and educate their childrenget a good education. Good quality education will make the children in the familywas able to infiltrate the globalization movement that had been made man to bematerialistic at all end of life. Barometer of all the activities he did more orientto the achievements of the material alone. So in the end, the quality of educationbeing taught more point out to the objectification of the material rather thanspiritual fulfillment. In this situation, the education that starts from the family willfortify all the pace of globalization that is becoming more effective and valuable.